The heterogeneity of self-employment: The example of Asians in the United States - John Lunn; Todd P. Steen (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2000)
Self-employment rates differ widely across industries and across racial and ethnic categories. The former is relatively easy for economists to explain while the latter differences are more difficult. Self-employment is rare in industries for which production is characterized by substantial economies of scale. Self-employment is more common in services than in manufacturing, although it is greatest in agriculture. There are also substantial differences in self-employment across countries, with the evidence suggesting an inverse relationship between self-employment and economic development. For the United States, self- employment rates tend to be higher in less densely populated states because self-employment rates are greater when average firm size is smaller (Lunn and Steen, 2000). According to some people, differences in self-employment rates across racial and ethnic categories are due to discrimination. Self-employment rates are higher for whites than other racial/ethnic groups, and are higher for men than for women. The numerous programs initiated by state and local governments to assist minority- and women-owned businesses usually offer discrimination against minorities and women as a rationale for the programs. However, self-employment rates often differ widely across more narrowly defined groups within broader racial or ethnic classifications. Within the United States, there is a relatively large gap between self-employment rates of Mexicans and Cubans, and a larger gap between Koreans and Laotians. Fairlie (1996) reports self-employment rates for Russians of 24.9 percent and 10.5 percent for Belgians. These differences in self-employment rates within broader classifications (Hispanics, Asians, and Europeans) suggest that discrimination may not be the primary cause. In this paper, we examine self-employment rates among various ethnic groups within the broader classification of Asian to illustrate the heterogeneity of the self-employed, and to discuss the implications of this heterogeneity.
Keywords: 330